Dosen Otoritatif: Analisis Persepsi Mahasiswa STIE Balikpapan - Puspita, Ephine Khaylilla; Tsalisa, Syafarani; Pranata, Raynaldi; Anhar (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to investigate student’s perceptions of authoritative teachers, commonly referred to as "killer" lecturers, in the context of the teaching and learning process, communication, and the lecturer’s assessment standards. The research employs a qualitative descriptive approach. The study was conducted at the STIE Balikpapan campus, with subjects being fifth-semester students from the Faculty of Business Economics. Data collection was carried out using semi-structured questionnaires containing open-ended questions to explore students views in depth. The results indicate that students perceive "killer" lecturers as strict, difficult to joke with, having high assessment standards, and engaging in minimal interaction. The study also highlights how effective collaborative and interactive teaching styles can create a conducive learning environment to achieve established educational goals